Inequalities, Territories and Vulnerabilities in the Development of Latin America (1990-2015) - Iglesias Lesaga, Esther; Carmona Motolinia, José Ramón (Sociedad y Economía, 2016)
This essay proposes rethinking inequalities and vulnerabilities in different territories andvarious situations which acquires the development of Latin America in the 1990-2015 period.A theoretical analysis on the subject is presented, and subsequently the study is implementedbased on certain indicators applied to some territories of Latin America. The topic is organizedinto three parts. The first one addresses the issues of inequality, development, vulnerabilityand democracy at the theoretical level. In the second part, we analyze the problems of growthand unemployment in Latin America during the period of analysis. Finally, the vulnerabilitiesgenerated by inequality are referred from the concepts of economic growth and development.Final reflections close this analysis and propose new questions about the topic.